How to stay healthy and foster well-being with narratives, or: Where narratology and salutogenesis could meet - Nünning, Vera; Nünning, Ansgar (How to do things with narrative, 2018)
Das Kapitel How to Stay Healthy and Foster Well-Being with Narratives, or: Where Narratology and Salutogenesis Could Meet erschien in How to Do Things with Narrative auf Seite 157.